Studi korelasional antara kebiasaan membaca dan penguasaan tata bahasa dengan keterampilan menulis deskripsi kelas V sekolah dasar - Yustika Eskasalma Nur Saffana; St. Y. Slamet; Tri Budiharto (Didaktika Dwija Indria, 2021)
This study aims to (1) determine whether there is a relationship between reading habits and description writing skills; (2) the relationship between grammar mastery and description writing skills; (3) the relationship between reading habits and mastery of grammar with description writing skills. This research uses a correlational method. The sample consisted of grade V students in 10 elementary schools, totaling 212 students. The data collection techniques used a descriptive writing test, a multiple choice test for grammar mastery, and a questionnaire for reading habits variable. Data were analyzed using simple correlation and multiple correlation. Based on the results of data analysis, the following conclusions are obtained: (1) there is a significant relationship between reading habits and description writing skills, ry1 = 0.606. The correlation coefficient tested using the t test, tcount = 11.0464 > ttable = 1.9713. (2) there is a significant relationship between grammar mastery and description writing skills with ry2 = 0.697, the significance of the correlation coefficient is calculated using the t test, tcount = 14.0993> ttable = 1.9713. 3) there is a significant relationship between reading habits and grammar mastery with descriptive writing skills as much as ry12 = 0.779. The results of the significance test using the F test showed that the Fcount = 161.88> Ftable = 3.0391 obtained from the Ftable with df 209 level α = 0.05. So it can be concluded that reading habits and grammar mastery have a significant relationship with description writing skills.